2011
DOI: 10.1016/j.inhe.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of Trinidadian households regarding leptospirosis and related matters

Abstract: Leptospirosis is a zoonotic disease that is underreported in many countries, including Trinidad and Tobago, because of a low level of awareness of the disease. A knowledge, attitudes and practices (KAP) survey concerning leptospirosis was carried out on 800 households throughout Trinidad to determine the level of awareness of the disease in the country. Of the participants, 52.4% had heard of leptospirosis but approximately half of these did not know any signs or symptoms of the disease. Knowledge of leptospir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 17 publications
9
21
2
4
Order By: Relevance
“…Further studies should actively look for the factors avoiding preventive practice of leptospirosis as behavior depends on many other factors beside knowledge and attitude. A surprising finding by a study in Trinidad and Tobago done involving 800 households showed that there was a positive attitude towards general health and good sanitary practices among them, although there was also a lack of knowledge of leptospirosis [12]. This finding was contradicted to the finding in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Further studies should actively look for the factors avoiding preventive practice of leptospirosis as behavior depends on many other factors beside knowledge and attitude. A surprising finding by a study in Trinidad and Tobago done involving 800 households showed that there was a positive attitude towards general health and good sanitary practices among them, although there was also a lack of knowledge of leptospirosis [12]. This finding was contradicted to the finding in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The weakest area identified in safe work practice sub domain was related to personal hygiene, which was covered by item that related to hand washing before sleeping and bathing in the river. Previous study also shared the same finding as our study whereby the respondents weakest area was related to personal hygiene [12]. For the general practice off work, the weakest area identified was struggling with flood water.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It can be understood because a person's level of education will determine the level of knowledge, attitudes and behavior in fighting the disease. Knowledge about the incidence, risk factors and preventive measures are often not owned by residents with low education, including the leptospirosis disease (Mohan, 2011).…”
Section: Resultsmentioning
confidence: 99%